2011
DOI: 10.1159/000323959
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of Cold Snare Polypectomy and Conventional Polypectomy for Small Colorectal Polyps

Abstract: Background and Aim: The ideal method to remove small colorectal polyps is unknown. We compared removal by colon snare transection without electrocautery (cold snare polypectomy) with conventional electrocautery snare polypectomy (hot polypectomy) in terms of procedure duration, difficulty in retrieving polyps, bleeding, and post-polypectomy symptoms. Methods: Patients with colorectal polyps up to 8 mm in diameter were randomized to polypectomy by cold snare technique (cold group) or conventional polypectomy (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(177 citation statements)
references
References 24 publications
8
161
0
5
Order By: Relevance
“…In the same study, although there was no relationship between the localization of polyps, the incidence of the risk of bleeding was related to the size of the polyps (6-9 mm) and the use of an antiplatelet agent. In another study, bleeding was not observed in patients who were not using an antiplatelet agent (15). In our study, there was no perforation, and in both groups, one patient had bleeding that required endoscopic treatment.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In the same study, although there was no relationship between the localization of polyps, the incidence of the risk of bleeding was related to the size of the polyps (6-9 mm) and the use of an antiplatelet agent. In another study, bleeding was not observed in patients who were not using an antiplatelet agent (15). In our study, there was no perforation, and in both groups, one patient had bleeding that required endoscopic treatment.…”
Section: Discussionsupporting
confidence: 45%
“…Therefore, these parameters were thought to affect the real time of the polypectomy. Unlike in another study (15), only the polypectomy time was measured in this study. The mean polypectomy time was significantly shorter with cold snare polypectomy versus hot snare polypectomy (p<0.001).…”
Section: Aslan Et Al Treatment Of Small Colonic Polypsmentioning
confidence: 99%
“…Th is relates entirely to the high prevalence of these lesions because increasing polyp size and proximal colon location are the major risk factors for bleeding per individual resected polyp ( 71 ). Cold resection techniques are eff ective and nearly devoid of clinically signifi cant bleeding risk and can be generally advised for nonpedunculated lesions <1 cm in size ( 72 ). Despite these risks, colonoscopy is the preferred approach to management of any benign colorectal polyp regardless of size or location because the alternative of surgical resection has higher mortality and cost compared with colonoscopy ( 73,74 ).…”
Section: Screening Targetsmentioning
confidence: 99%
“…Fujiya et al [1] showed by a meta-analysis that the average procedural time for CP was significantly shorter than that for hot polypectomy (HP) group. Several studies have shown that post-polypectomy bleeding (PPB) is less common with CP than with conventional polypectomy [2-4]; however, there have been few studies about PPB in patients who underwent to CP and who were taking antithrombotic drugs. According to the 2012 update of the Japanese guidelines for periprocedural management of patients taking antithrombotic medications issued by the Japan Gastroenterological Endoscopy Society [5], procedures with a low risk of hemorrhage may be performed with a short interruption or continuation of antithrombotic medication.…”
Section: Introductionmentioning
confidence: 99%